8 - Militantisme Politique et Entrepreneuriat :: relations de dépendance et enjeux dans le contexte Camerounais - Valentin Ngouyamsa, (African Sociological Review, 2016)
In Cameroon, the strong involvement of entrepreneurs in the political field is reflected in a strong political activism. There is a strong dependence between the entrepreneurial world and the political world. Political circles allow politicians to develop networks that not only protect and manage their affairs, but also generate real capital. In return, the capital generated fuels political power. Interviews with about thirty small entrepreneurs in the city of Dschang, entrepreneurship and innovative thinking are the activities that really apply only to men of political success and are of no interest to the ordinary citizen. The stakes of this dependence are certain because if the engine of development is the capacity to perceive economic opportunities and grasp them, political freedom and freedom of enterprise must rhyme and contribute to the development of the economy of a nation.